Integration of Environmental Sustainability Issues In Design Education Curriculum - Kafaridou, Marianna; Kazamia, Kika Ioannou (European Journal of Sustainable Development, 2023)
An early acquirement of knowledge on sustainability can bring a change in how young people act. The focus of this paper is first to evaluate the current knowledge of first year design students on environmental sustainability and second to assess if students consider environmental issues in the approach and resolution of a design project. The research elaborates through a questionnaire given to students of the graphic and digital design program and interior design program which result in a quantitative and qualitative understanding of the focus of the research. Sustainability - based on environmental, social, and economic pillars - is a big concern in the design discipline. Moreover, environmentally sustainable issues are of great importance in design education curricula as most of the design briefs that students receive require the inclusion of sustainability issues. According to the results, this research will attempt to propose the design and implementation of an introductory course for first year students of both programs. The educational benefits of an early introduced course on sustainability are essential for developing the designer’s perception of the design scheme today. Keywords: sustainability, design, education, environment, course.